A Training-Model Scale’s Validity and Reliability Coefficients: Expert Evaluation in Indonesian Professional Psychology Programs - Ningdyah, Anrilia E. M.; Greenwood, Kenneth Mark; Kidd, Garry (Makara Human Behavior Studies in Asia, 2018)
Very little information has been available on training models in professional psychology programs in Indonesia, despite the IndonesianNational Accreditation Body recommending that scientist-practitioner models be applied in the education of psychologists. By contrast, research abounds on such training models in Western countries. This discrepancy raises the importance of developing a measurement tool appropriate for assessing training models in Indonesian professional psychology programs. This article describes the process of testing the validity and reliability of such a training model measuring tool in the Indonesian context. The authors used the expert evaluation method and the Aiken formula to calculate a coefficient of content validity and item’s internal consistency reliability. This process formed a training model scale comprising 77 items with satisfactory validity and reliability indexes for measuringIndonesian professional psychology program training models.